Modeling the interaction of terahertz pulse with healthy skin and basal cell carcinoma using the unconditionally stable fundamental ADI-FDTD method - Heh, Ding Yu (2020)
—This paper presents the application of unconditionally stable fundamental finite-difference time-domain (FADI-FDTD) method in modeling the interaction of terahertz pulse with healthy skin and basal cell carcinoma (BCC). The healthy skin and BCC are modeled as Debye dispersive media and the model is incorporated into the FADIFDTD method. Numerical experiments on delineating the BCC margin from healthy skin are demonstrated using the FADI-FDTD method based on reflected terahertz pulse. Hence, the FADI-FDTD method provides further insight on the different response shown by healthy skin and BCC under terahertz pulse radiation. Such understanding of the interaction of terahert pulse radiation with biological tissue such as human skin is an important step towards the advancement of future terahertz technology on biomedical applications.